Implementation of Lean Construction to Eliminate Waste: A Case Study Construction Project in Indonesia - Harpito; Wresni Anggraini; Merry Siska; Dian Novitri (Department Industrial Engineering, University of Muhammadiyah Malang, 2022)
Lean Construction (LC) presented innovative practices to maximize the production value and minimize the production waste during construction. The problem that frequently occurs in the project is delaying the schedule, leading to time and cost overrun. This research aims to eliminate waste that causes delay and inefficiency. Several LC techniques were carried out to improve the efficiency of this project, namely: Value Stream Mapping (VSM) to discover wastes and determine Process Efficiency Cycle (PCE); Waste Assessment Model (WAM) to identify the inter-relationship among wastes; Fishbone (Ishikawa) diagram analysis to get the root cause of the waste. Research results showed the three highest wastes: defect 14.06%, over production 21.44%, and the highest rank was unnecessary inventories 31.73%. After implementing LC techniques, the PCE increased from 72 % to 79%. The implication of this research is to provide recommendations to the project’s stakeholders in running the building construction to avoid delay and inefficiency.